COMPUTER MEDIATED COMMUNICATION (Ustozlar uchun, 2026)
This article discusses the concept of Computer-Mediated Communication (CMC) and its role in modern communication and language learning. It explains the main types of CMC, including synchronous and asynchronous communication, and highlights their importance in improving language skills. The article also examines the advantages, such as accessibility and flexibility, as well as the disadvantages, including technical issues and lack of non-verbal cues. Overall, CMC is presented as an effective tool for global interaction and education.